THE PERCEPTION OF PRIMARY SCHOOL TEACHERS OF ONLINE LEARNING DURING THE COVID-19 PANDEMIC: A CASE STUDY UPT SPNF SKB ENREKANG, INDONESIA - Hasmiwarni Hasmiwarni; Elihami Elihami (Universitas Muhammadiyah Enrekang, 2021)
The online learning system is a solution for the teaching and learning process during the COVID-19 pandemic for all levels of education, including early childhood education (PAUD). The purpose of the study was to obtain an overview of the effectiveness of online learning at the Early Childhood Education (PAUD) level, to explain the obstacles and solutions for PAUD teachers in providing online learning, and to explain the efforts of teachers in developing PAUD learning in the Covid Era. The research subjects were two educators at PAUD UPT SPNF SKB ENREKANG. Qualitative research design using interview techniques in collecting data. The results of the study show that the teaching and learning process is carried out online even though the learning becomes ineffective due to obstacles including the lack of student motivation and lack of facilities such as cellphones and internet quotas. One solution is offline learning. Paying attention to aspects of learning as a teacher's effort to achieve learning.